Trust and switching cost as a way to build e-loyalty in internet markets. (4th October 2004) - Lee, Dong-Il; Sohn, Changsoo
As the expectations from e-business have changed to disappointment, many e-business companies are trying to survive in internet markets. As a way to survive in the market, they try to build customers' loyalty by emphasising trust. On the other hand, they set high switching costs in order to lock-in customers. Few studies have empirically conducted the test to verify that trust and switching costs are the most critical components for building customer loyalty. This study, based on survey analysis and structural equation modelling, revealed that trust is the main factor for building customers loyalty, rather than switching costs.